2008
DOI: 10.1097/brs.0b013e3181788704
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Coplanar Alignment

Abstract: VCA provided excellent correction of coronal and transverse planes with normalization of thoracic kyphosis in Lenke type 1 adolescent idiopathic scoliosis surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Bilateral apical vertebral derotation by vertebral column manipulation (VCM) was introduced by Chang and Lenke [13] using a “quadrilateral frame” to bilaterally simultaneously manipulate the spine, thereby effectively correcting 3D deformities present in IS. Vertebral coplanar alignment (VCA) was described by Vallespir [14] who utilized the coplanar nature of the x - and z- axes of the spine to correct translation and rotation in patients with scoliosis. Clinical studies have demonstrated the effectiveness of 3D correction for IS using VCA [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral apical vertebral derotation by vertebral column manipulation (VCM) was introduced by Chang and Lenke [13] using a “quadrilateral frame” to bilaterally simultaneously manipulate the spine, thereby effectively correcting 3D deformities present in IS. Vertebral coplanar alignment (VCA) was described by Vallespir [14] who utilized the coplanar nature of the x - and z- axes of the spine to correct translation and rotation in patients with scoliosis. Clinical studies have demonstrated the effectiveness of 3D correction for IS using VCA [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral coplanar alignment (VCA) was described by Vallespir [14] who utilized the coplanar nature of the x - and z- axes of the spine to correct translation and rotation in patients with scoliosis. Clinical studies have demonstrated the effectiveness of 3D correction for IS using VCA [14,15]. However, few reports to date have compared the bilateral apical vertebral derotation technique by VCM to the VCA technique as assessed by radiographic, functional, and outcome parameters, and technical features in patients with IS.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have also shown that PS constructs produce a significantly better vertebral derotation effect than hook-and-rod constructs [5,6,17]. The mean derotation angle obtained with a PS construct is reported to be 7.1-13.0° [5,18,19], while it is 0.4°-3.6° [20-26] with a hook-and-rod construct and 1.9°- 4.2° with the sublaminar wiring technique [27,28]. We therefore hypothesized that the decrease in thoracic kyphosis after posterior correction surgery using PS constructs was associated with the correction of vertebral rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Vellespir et al 13 has shown a curve correction of 73% in their thoracic curves and 70% in thoracolumbar curves with the technique of vertebral coplanar alignment. The latter technique involves vertical slotted tubes attached to the convex screws and longitudinal rod is put in gradually to the convex side so that the rotated vertebrae all come in one plane.…”
Section: Discussionmentioning
confidence: 99%